Spatial cognition and the death metaphor in the Hebrew Bible - Lamprecht, Adriaan (University of the Free State, 2015)
ENGLISH: This study introduces a cognitive semantic approach to Biblical Hebrew linguistics with important implications for Biblical Hebrew semantic study, Biblical Hebrew lexicography, Bible interpretation and translation, and Conceptual Metaphor theory. Traditionally, the semantics of spatial-motion verbs in Biblical Hebrew has been interpreted in accordance with comparative, historical-comparative and structural approaches towards language. Consequently, the meanings of these spatial-motion verbs appear incoherent and arbitrary. This apparent gap between the so-called ‘discovery procedures’ that the Biblical Hebrew linguist should in practice adopt when facing a corpus of data for analysis and the meaning of the spatial-motion verbs, is bridged by applying the cognitive semantic approach to the analyses of the spatial motion verbs dry (jrd) and hl[ (`lh) in the Hebrew Bible. This is done in order to support the hypothesis that these verbs carry non-metaphorical (literal) meanings and metaphorical meanings, and that the linguistic processing of DEATH as an abstract concept involves activation of spatial systems. The study has three main parts. The first part (Chapter 3) reflects on the ancient Israelites’ conceptualisation of space which attempts to employ spatial cognition to uncover conventional image schematic patterns, categorisations and FRAMES at the conceptual level in order to understand the spatial motion verbs dry (jrd) and hl[ (`lh) and their related encyclopaedic knowledge systems. The second part (Chapters 4-5) focuses on the mental processes and semantic structure encoded by the spatial motion verbs dry (jrd) and hl[ (ˊlh) in context of use. In the last instance (Chapter 6), the study explores the concept of DEATH within the context of its essential and relational motion and spatial expressions. The study finds that the knowledge structures used by the ancient Israelites include image schemas, a spatial frame of reference, cognitive map knowledge and a HEAVEN-EARTH-SHEOL frame. The analyses of the data show that far from being solely topological, the primitives of dry (jrd) and hl[ (ˊlh) are packed with derived meaning; and that by unpacking these meanings we can shed light on the ancient Israelites’ spatial experiences, ideological presuppositions, cultural beliefs and abstract reasoning. Furthermore, the analyses of the data show that the verbs dry (jrd) and hl[ (ˊlh) can shift meanings in different contexts of use. The shift from the literal to the metaphorical aspects of the lexical meaning of the verbs dry (jrd) and hl[ (ˊlh) involves image schemas, FRAMES and binary structures found in the linguistic system and the conceptual system. An important finding regarding the ancient Israelites’ conceptual system is that abstract concepts are systematically structured in terms of conceptual domains deriving from their experience involving properties like motion in horizontal and vertical elevation, containment, structures and the body. The verbs dry (jrd) and hl[ (ˊlh) are mainly used for the conceptualisation of changes in the following target domains: HIERARCHY, BEHAVIOUR, QUANTITY, TIME and STATES. A discussion of certain narratives (Judges 11:37; 2 Kings 2:2; 2 Kings 2:11) validates the claim that abstract conceptual domains such as DEATH are structured by metaphorical mappings from more concrete experiential domains such as motion and space. Lastly, this study extends the existing knowledge of conceptual metaphor. Specifically, it expands the knowledge concerning verbs conflating a bipolar conceptual component, that is, MOTION and PATH. This study reveals that dry (jrd) and hl[ (ˊlh)’s bipolar lexical concept MOTION DOWN/UP may split into two unipolar lexical concepts MOTION and DOWN/UP in which only one unipolar lexical concept, that is DOWN/UP, is used for metaphorical conceptual mapping. AFRIKAANS: Hierdie studie gebruik ‘n kognitief-semantiese benadering tot Bybel-Hebreeuse linguistiek wat belangrike implikasies inhou vir Bybel-Hebreeuse semantiese studie, Bybel-Hebreeuse leksikografie, Bybelinterpretasie- en vertaling en Konseptuele Metafoor-teorie. Die semantiek van ruimtelik-bewegingswerkwoorde in Bybel-Hebreeus is tradisioneel in navolging van vergelykende-, histories-vergelykende- en strukturele benaderings tot taal bestudeer. Die betekenis van hierdie ruimtelik-bewegingswerkwoorde vertoon gevolglik ŉ inkonsekwente en arbitrêre karakter. Hierdie herkenbare gaping tussen die sogenaamde ‘ontdekkings prosedures’ wat die Bybel-Hebreeuse taalwetenskaplike in praktyk moet aanwend wanneer hy/sy ‘n databasis bestudeer, en daarmee saam die betekenis van die ruimtelik-bewegingswerkwoorde bepaal, word oorbrug deur die kognitief-semantiese benadering in die bestudering van die ruimtelik-bewegingswerkwoorde dry (jrd) en hl[ (`lh) in die Hebreeuse Bybel aan te wend. Dit word gedoen om die hipotese, naamlik dat hierdie werkwoorde ‘n nie-metaforiese (letterlike) en ‘n metaforiese betekenis vertoon, en ook dat die taalkundige beskrywing van die DOOD as abstrakte konsep die aktivering van ruimtelike sisteme insluit, te ondersteun. Die studie word volgens drie hoofdele georden. Die eerste afdeling (Hoofstuk 3) gee aandag aan die antieke Israeliete se konseptualisering van ruimte en poog om ruimtelike kognisie te gebruik om konvensionele beeldskema patrone, kategorisering en RAAMWERKE op konseptuele vlak bloot te lê. Die doelwit hiervan is om die ruimtelike-bewegingswerkwoorde dry (jrd) en hl[ (`lh) en hul verwante ensiklopediese kennissisteme te verstaan. Die tweede afdeling (Hoofstukke 4-5) fokus op die kognitiewe prosesse en semantiese struktuur wat deur die ruimtelike-bewegingswerkwoorde dry (jrd) en hl[ (ˊlh) in konteks van gebruik blootgelê word. In die laaste afdeling (Hoofstuk 6) bestudeer hierdie studie die konsep DOOD in die konteks van die konsep se fundamentele en verbandhoudende bewegings- en ruimtelike uitdrukkings. Die studie bevind dat die kennisstrukture wat deur die antieke Israeliete gebruik is die volgende insluit: beeldskemas, ŉ ruimtelike verwysingsraamwerk, ŉ kognitiewe kaart kennis en ŉ HEMEL-AARDE-SHEOL raamwerk. Die bestudering van die data toon dat die basiese betekenis van dry (jrd) en hl[ (ˊlh) nie alleenlik topologies van aard is nie, maar dat die basiese betekenis ryk is aan afgeleide betekenis. Deur hierdie betekenismoontlikhede bloot te lê kan ŉ mens meer lig werp op die antieke Israeliete se ruimtelike waarnemings, ideologiese voorveronderstellings, kulturele idees en abstrakte denkepatrone. Verder, die bestudering van die data toon dat die werkwoorde dry (jrd) en hl[ (ˊlh) hul betekenisse in verskillende gebruiks-kontekste kan aanpas. Die verplasing vanaf die letterlike na die metaforiese aspekte van die leksikale betekenisse van die werkwoorde dry (jrd) en hl[ (ˊlh) sluit beeldskemas, RAAMWERKE en binêre strukture in wat in die linguistiese sisteem en die konseptuele sisteem gevind is. ‘n Belangrike bevinding ten opsigte van die antieke Israeliete se konseptuele sisteem is dat abstrakte konsepte sistematies gestruktureer is in terme van konseptuele domeine wat afleibaar is van hul belewenis van beweging in horisontale- en vertikale ruimte, beweging in houers, beweging van strukture en die beweging van die liggaam. Die werkwoorde dry (jrd) en hl[ (ˊlh) word hoofsaaklik gebruik vir die konseptualisering van verandering in die volgede domeine: HIËRARGIE, GEDRAG, KWANTITEIT, TYD en STATUS. ‘n Bespreking van sekere verhale (Rigters 11:37, 2 Konings 2:2, 2 Konings 2:11) bevestig die aanname dat abstrakte konseptuele domeine soos DOOD gestruktureer is deur metaforiese passings van konkrete belewenis-domeine soos beweging en ruimte. Laastens, die studie verbreed die bestaande kennis van konseptuele metafore. Meer spesifiek, die studie verbreed die kennis met betrekking tot werkwoorde wat ‘n bipolêre konseptuele komponent vertoon, naamlik BEWEGING en ROETE. Die studie toon dat dry (jrd) en hl[ (ˊlh) se bipolêre konseptuele komponent BEWEGING AF/OP kan verdeel in twee een-kantige leksikale konsepte BEWEGING en AF/OP waarin net een een-kantige leksikale konsep, naamlik AF/OP gebruik word vir metaforiese konseptuele passing.
Keywords: Spatial cognition; Hebrew Bible; Sheol; Elijah; Cognitive linguistics; Cognitive semantics; Unipolar conceptual metaphor; Thesis (Ph.D. (Hebrew)) - University of Free State, 2015